PENGARUH SIKAP DAN NORMA SUBJEKTIF TERHADAP NIAT MENGELUH PELANGGAN HOTEL 100 SUNSET 2 - Citra Prahastuti, Ni Putu; Gede Suasana, I Gusti Agung Ketut (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
The aim of the study to determine the influence of attitude and subjective norm against the customer complains intention 100 Sunset 2 hotels in Kuta. This study was conducted on 100 Sunset 2 hotels in Kuta. The samples used were 100 respondents with non - probability sampling method is purposive sampling. Data collected through questionnaires. Data were analyzed using multiple regression analysis. The results found that the attitude and subjective norm positive and significant effect on the intention customer complains on 100 Sunset 2 hotels in Kuta. 100 Sunset 2 hotels in Kuta should be able to provide the best service for customers that attitude and subjective norm becomes positive customer so that the customer intention to complain reduced.
Keywords: Attitude, Subjective Norm, Complaining Intentions